The Production And Purification Of D6 And Darc Chemokine Decoy Receptor Recombinant Proteins And Their Effects On Migration And Invasion In Mda-Mb-231 And Mcf-7 Cells - Tan, Wee Yee (2018)
D6 and DARC had been reported as a decoy chemokine receptor in cancer study. The involvement of D6 and DARC in breast cancer had been investigated and it was reported to negatively correlate with the progression and metastasis of breast cancer cells. This study aimed to construct recombinant clones of D6 and DARC, express, analyze and purify the proteins and then determine the effects of the recombinant proteins on breast cancer cell migration and invasion. D6 and DARC genes in MDA-MB-231 cell line were first amplified by one-step RT-PCR with gene specific primers and Pfu DNA polymerase. Besides, DARC was also amplified by PCR using Phusion DNA polymerase. For each of the clones, two pairs of specific primers were used to generate full length nucleotide sequences which were cloned into pPICZ and pPICZα expression vectors.